1984
DOI: 10.1152/jn.1984.52.2.290
|View full text |Cite
|
Sign up to set email alerts
|

Influence of globus pallidus on arm movements in monkeys. I. Effects of kainic acid-induced lesions

Abstract: The role of basal ganglia output via the globus pallidus (GP) was examined in monkeys trained to make rapid arm-reaching movements to a visual target in a reaction-time task. When neurons in the globus pallidus were destroyed by injection of kainic acid (KA) during task execution, contralateral arm movement times (MT) were increased significantly, with little or no change in reaction times (RT). The slowed movements were associated with a generalized depression in the amplitude and rate of rise of electromyogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
60
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(73 citation statements)
references
References 0 publications
13
60
0
Order By: Relevance
“…For example, it helps to explain how motor expectations (pattern) interact with volitional speed signals (energy) to generate goaldirected arm movements [89][90][91] , as during the computation of the Desired Velocity Vector in the cortical area 4 circuit of Figure 6. As noted in the discussion of 'where' and 'how' processing, a motor expectation represents where we want to move, such as to the position where our hand can grasp a desired object.…”
Section: Motor Expectation and Volitionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it helps to explain how motor expectations (pattern) interact with volitional speed signals (energy) to generate goaldirected arm movements [89][90][91] , as during the computation of the Desired Velocity Vector in the cortical area 4 circuit of Figure 6. As noted in the discussion of 'where' and 'how' processing, a motor expectation represents where we want to move, such as to the position where our hand can grasp a desired object.…”
Section: Motor Expectation and Volitionmentioning
confidence: 99%
“…Such a motor representation, or Target Position Vector (TPV), can prime a movement, or get us ready to make a movement, but by itself, it cannot release the movement 55,89 . First the TPV needs to be converted into a Difference Vector (DV), which triggers an overt action only when a volitional signal 90 that multiplicatively gates action read-out. The volitional signal for controlling movement speed is called a GO signal, as in Figure 6.…”
Section: Motor Expectation and Volitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have reported that PD patients have an inherent limitation in the rate at which they can develop force during rapid and discrete isometric contractions [25,29]. Damage to basal ganglia structures has been shown to produce abnormalities in force recruitment [17,18] and such abnormities are often compensated for by lengthening impulse duration to augment force output [1,16]. Recent studies using neuroimaging techniques in human have demonstrated that the internal segment of the globus pallidus and subthalamic nucleus in basal ganglia nuclei are directly related to the force development speed during isometric force production [28].…”
mentioning
confidence: 99%
“…The DV is multiplied by a gradually increasing GO signal, that is under volitional control, whose growth rate can be changed to alter movement speed while preserving movement direction and length ( Figure 1). The "GO" signal seems to be generated with in the basal ganglia (Hallett & Khoshbin, 1980;Georgopoulos et a!., 1983;Horak & Anderson, 1984a, 1984bBcrardclli eta!., 1996;Turner & Anderson, 1997;Turner ct a!., 1998). The DV times the GO signal is an outflow representation of movement velocity that is integrated at the PPV until the present position of the hand reaches the target.…”
Section: The Vite Model Of Reachingmentioning
confidence: 99%